Isomers and electronic states of Ni2O2H2 and evaluation of the effect of charge on the electronic properties and reactivity of Ni2O2 - Hübner, Olaf; Himmel, Hans-Jörg (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2013)
Different isomers of Ni2O2H2 are investigated by multireference configuration interaction (MRCI) calculations, based on complete active space self-consistent field (CASSCF) calculations. The lowest-lying Ni2(OH)2 isomer has a rhombic shape with two OH- groups bridging two NiI ions. Its ground term is a 1Ag term. At a relative energy of 1.06 eV, there is a chain-like NiONi(OH2) isomer. A rhombic (NiH)2O2 isomer with Ni-H bonds has a considerably higher energy of 2.93 eV. Both Ni2(OH)2 and NiONi(OH2) feature a large number of low-lying electronic terms that in the case of Ni2(OH)2 form Heisenberg spin ladders due to the coupling of the electrons of two NiI ions (3d84s1) with S = 3/2. For the reaction Ni2O2 + H2 → Ni2(OH)2, the reaction energy is estimated to −2 eV. Finally, neutral and charged Ni2O2 and their hydrogenation products (Ni2O2H20/+) are compared.